Emisi Gas Rumah Kaca dan Cadangan Karbon pada Perkebunan Kopi Organik dan Konvensional di Kabupaten Badung, Bali - Ika Ferry Yunianti; I.D.A Yona Aprianthina; Rina Kartikawati; Eni Yulianingsih (Pusat Penelitian dan Pengembangan Perkebunan, 2021)
Coffee is a commodity that has an important role in the national economy. Currently, coffee cultivation is threatened by climate change caused by global warming due to increased green house gas (GHG) emissions. The organic plantation model is a farming model that is considered to increase soil and crop productivity, reduce GHG emissions, and increase carbon sequestration effectively. The study was aimed to estimate GHG emissions and carbon stocks in organic and conventional coffee plantations in Badung Regency, Bali Province and Laboratory in Balai Penelitian Lingkungan Pertanian, Pati, Jawa Tengah Province, in July 2018. The study was conducted in smallholder coffee plantations in Badung Regency and the analysis was carried out at Laboratory of Indonesian Agricultural Environtment Research Institute. This study used a survey method, while the sampling used a purposive sampling method in organic and conventional coffee plantation. GHG emissions measurement was carried out with a close chamber method by simultaneously the carbon stocks measurement was carried out with the non-destructive method for plant biomass and destructive for understorey. The results showed that organic and conventional coffee plantations emitted GHG by 20.71 and 39.75 ton CO2e ha-1 and stored carbon stock by 227.56 and 288.31 ton CO2e ha-1, respectively. The differences in GHG emissions and carbon stocks are partly due to differences in management system and the diversity of plant. The management system of the organic coffee plantation should be improved to support handling of the impacts of climate change in Bali Province.